Speech aspect of information behavior - Tazapchiyan Rafail; Shapovalova Elena (E3S Web of Conferences, 2021)
This article is devoted to the analysis of information behavior based on the use of a natural language to obtain information by reading a literary text in a non-native language. One of the options for the result of such behavior is the so-called communication failures, which indicate obstacles in information retrieval. By communicative failures, the authors of the article mean a failure in the communication process, when the produced speech act does not fulfill its intended function, the addressee gets a greater degree of freedom to interpret the message sent to him, and his reaction may either not coincide with the one that was planned by the sender, or contradict it. In this case, culture acts as a regulator of information behavior as a set of values circulating in a social community. The mechanisms of the influence of culture on the mentioned behavior are stereotypes that exert a typifying influence on the activity of an individual. An attempt was made in the article to analyze the nature of the detected communication failures, as well as their typological description.